1961
DOI: 10.1177/004051756103101107
|View full text |Cite
|
Sign up to set email alerts
|

Part V: The Nature of Birefringence

Abstract: The birefringence of Corriedale wool fibers was measured at nine different relative humidities. After being corrected for swelling the curve of birefringence against mois ture content showed a minimum at a moisture content of 19% of the dry weight of the wool. At this point the birefringence is probably completely intrinsic, but at other moisture contents there may be a component of environmental birefringence. The curve shape may also be due in part to change of intrinsic birefringence with change of moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1966
1966
1987
1987

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The decrease of hi with the aliphatic chain length n was expected from other mechanical data [4] that showed that the work to extend a wool fibre in alcohol/water (50:50) mixtures, related to the stress level in the yield region, drops approximately linearly with increasing aliphatic chain length of the alcohol. Since the phase M is very weak in water most of the stress and hence the stress drop originates in the phase C. This falls in line with the X-ray data [8] which show an increased swelling of the crystalline phase and with birefringence data [7] which show decreasing fiber birefringence equivalent to a decreasing difference between the phases with increasing aliphatic chain length of the alcohol.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The decrease of hi with the aliphatic chain length n was expected from other mechanical data [4] that showed that the work to extend a wool fibre in alcohol/water (50:50) mixtures, related to the stress level in the yield region, drops approximately linearly with increasing aliphatic chain length of the alcohol. Since the phase M is very weak in water most of the stress and hence the stress drop originates in the phase C. This falls in line with the X-ray data [8] which show an increased swelling of the crystalline phase and with birefringence data [7] which show decreasing fiber birefringence equivalent to a decreasing difference between the phases with increasing aliphatic chain length of the alcohol.…”
Section: Discussionsupporting
confidence: 84%
“…Changes in the state of the main morphological components of wool under the influence of the alcohols are indicated by the change of the optical properties, e. g. of the birefringence of the fibers [7] and of the X-ray patterns [8]. The structural units of the wool fiber that give rise to the birefringence are assumed to be the ee-helical filaments in the fiber [9].…”
Section: Introductionmentioning
confidence: 99%